The effect of silica nanocapsules on self-healing concrete. (20th September 2021) - Apolinário de Oliveira, Tassiane; D'Orey Gaivão Portela Bragança, Mariana; Miguel Pinkoski, Igor; Carrera, Gilberto
Highlights: Concretes containing silica nanocapsules were tested for self-healing. The healing effect on mechanical properties and water absorption was analyzed. Crack filling and the formation of new products were monitored experimentally. Water was essential for the complete healing of concretes with silica nanocapsules. Abstract: Concrete mixtures containing silica nanocapsules underwent a cracking procedure and were exposed to a natural atmospheric environment and a humidity chamber for 180 days to analyze self-healing. Mechanical recovery was observed in both exposures with increases of 26.94% and 25.82% for the 6% content. A decrease in water absorption was detected in humidity chamber environment. Formation of albite in the cracks interior and silica nanocapsules were detected using XRD, indicating the addition disponibility to continuous healing. The concretes healed completely, verified by OM and FEG/SEM-EDS, after 180 days in the humidity chamber, proving the nanocapsules applicability in high humidity regions.